Associations between male infertility and ancestry in South Americans: a case control study - Maria Fernanda Skowronek; Tatiana Velazquez; Patricia Mut; Gonzalo Figueiro; Monica Sans; Bernardo Bertoni; Rossana Sapiro (BMC, 2017)
Abstract Background Infertility affects 15% of human couples, with men being responsible in approximately 50% of cases. Moreover, the aetiology of male factor infertility is poorly understood. The majority of male factor infertility remains idiopathic and potentially genetic in origin. The association of the Y chromosome and mitochondrial haplogroups with male infertility has been previously reported. This association differs between studied populations and their geographical distributions. These effects have been only rarely analysed in mixed populations, such as South Americans. Methods In this study, we analysed the contributions of the Y chromosome and mitochondrial haplogroups to male infertility in a mixed population. A case control study was conducted. Regular PCR and high-resolution-melting-real-time PCR were performed to type haplogroups from fertile and infertile men. The sperm parameters from infertile men were compared in each haplogroup by logistic regression analysis and ANOVA. Results The genotyping confirmed the known admixture characteristic of the Uruguayan population. The European paternal contribution was higher than the maternal contribution in both fertile and infertile men. Neither maternal nor paternal ancestry presented differences between the cases and controls. Men belonging to the Y chromosome haplogroup F(xK) more frequently presented with an abnormal sperm morphology than men from other haplogroups. The sperm parameters were not associated with the mitochondrial haplogroups. Conclusions The data presented in this study showed an association between male infertility and ancestry in the Uruguayan population. Specifically, abnormal sperm morphology was associated with the Y chromosome haplogroup F(xK). Since the Y chromosome lacks recombination, these data suggest that some genes that determine sperm morphology might be inherited in blocks with the region that determines specific haplogroups. However, the possible association between the Y chromosome haplogroup F(xK) and sperm morphology requires further confirmatory testing. Data linking infertility with ancestry are needed to establish the possible causes of infertility and define male populations susceptible to infertility. Whether the admixed characteristics of the Uruguayan population exert any pressure on male fertility potential must be further investigated.